Bombyx and Bugs in Meiji Japan: Toward a Multispecies History? - Onaga, Lisa A. (2016)
In the lively, experimental spirit of multispecies research, I explore how a broader view of the domesticated silkworm species, which includes the “bugs” that afflicted it, forces us to reenvision familiar histories of sericulture that centered upon the means and end of “silk making.” In this case, a “multispecies” history draws our attention to the materiality of the biotic world that humans and nonhumans cohabit in order to produce a more holistic view of what “make silk.” The essay looks beneath the shine and sheen of silk in order to consider different issues that stoked or promoted the production of raw silk as well as motivated the reach (or blockade) of this commodity to a predominantly North American market in the first half of the twentieth century. This requires a deliberation of the activities that went into making raw silk in Japan, especially a deeper recognition of the insect employed for this purpose, the domesticated silkworm, Bombyx mori, and its parasites. This closer, organism-centric look at textiles thus makes clear the critical value of asking why silk could be marshaled overseas on the scale that it did by the 1910s and 1920s.